Feasibility and efficacy of the Great Leaders Active StudentS (GLASS) program on children's physical activity and object control skill competency: A non-randomised trial. Issue 12 (December 2017) - Nathan, Nicole; Sutherland, Rachel; Beauchamp, Mark R.; Cohen, Kristen; Hulteen, Ryan M.; Babic, Mark; Wolfenden, Luke; Lubans, David R.
Abstract: Objectives: This study aimed to assess the feasibility and efficacy of the Great Leaders Active StudentS (GLASS) program, a school-based peer-led physical activity and object control skill intervention. Design: The study employed a quasi-experimental design. Methods: The study was conducted in two elementary schools, one intervention and one comparison, in Newcastle, New South Wales (NSW), Australia from April to June 2015 (N = 224 students). Peer leaders (n = 20) in the intervention school received training to deliver two 30-min object control skill sessions per week to students in Kindergarten, Grades 1 and 2 (5–8 years, n = 83) over one school term (10 weeks). The primary outcome was pedometer assessed physical activity during school hours. Secondary outcomes included students' object control skill competency and peers' leadership self-efficacy and teacher ratings of peers' leadership skills. Results: Almost all (19/20) GLASS sessions were delivered by peer leaders who reported high acceptability of the program. The treatment-by-time interaction for students' physical activity during school hours was not significant (p = 0.313). The intervention effect on students' overall object control skills was statistically significant (mean difference 5.8 (95% CI 4.1, 7.4; p < 0.001)). Teacher-rated peer leadership significantly improved (0.70; 95% CI 0.38–1.01); p < .001)). Conclusions: The GLASS program was found to be both feasible and acceptable. The intervention also resulted in improvements in students' overall object control skills as well as teacher-rated peers' leadership behaviours. Future fully powered trials using peer leaders to deliver fundamental movement skill (FMS) programs are warranted.